Management of intussusception in patients with melanoma. Issue 7 (7th February 2019) - Perez, Matthew C.; Sun, James; Farley, Clara; Han, Dale; Sun, Alexander H.; Narayan, Deepak; Lowe, Michael; Delman, Keith A.; Messina, Jane L.; Gonzalez, Ricardo J.; Sondak, Vernon K.; Khushalani, Nikhil I.; et al.
Abstract: Background: Increased cross‐sectional imaging for surveillance of metastatic melanoma has led to more diagnoses of asymptomatic intussusception. Methods: We performed a multi‐institutional retrospective review of patient records with a history of metastatic melanoma and a diagnosis of intussusception. Patients were divided into three groups: 1) asymptomatic patients without current evidence of melanoma (no evidence of disease [NED]); 2) asymptomatic intussusception and known active metastatic melanoma; 3) symptomatic intussusception and known active metastatic melanoma; the number of patients requiring surgery and intraoperative findings were recorded. Results: We reviewed 73 patients diagnosed with intussusception from 2004 to 2017. Among asymptomatic patients with NED (n = 16), 14 spontaneously resolved and 2 underwent pre‐emptive surgery without abnormal intraoperative findings. Of asymptomatic patients with active metastatic disease (n = 32), 25 were initially observed and 7 underwent pre‐emptive surgery and 9 of the 25 initially observed patients required surgery for development of symptoms. In this group, all 16 patients undergoing surgery (50% of the group) had intraoperative findings of intussusception and/or metastatic intestinal melanoma.. All symptomatic patients with metastatic melanoma (n = 25) underwent surgery; all had intraoperative findings of intussusception and/or metastatic melanoma except 1 (Meckel's diverticulum). Conclusion: Asymptomatic patients with NED do not require surgery and intussusception will likely resolve spontaneously. Asymptomatic patients with known metastatic melanoma may be initially observed, but a low threshold for surgery should be maintained. Symptomatic patients with known metastases should undergo surgery.